The Relationship of Hba1c Levels with Sexual Function Disorders in Patients with Diabetes Mellitus in the Internment Room of Prof. Dr. H. Aloei Saboe Hospital Gorontalo City - Yugita Achmad; Ita Sulistiani; Nirwanto K. Rahim (Universitas Muhammadiyah Palu, 2026)
HbA1c is the result of glycemic control of DM patients over the last 2–3 months, so it is more accurate than just using a momentary blood glucose test. Poor HbA1c control has a significant impact on a variety of complications, including impaired sexual function. Sexual dysfunction in diabetic patients is not only influenced by physiological factors, but also by psychosocial factors such as depression, anxiety, and sexual self-perception disorders (sexual self-concept. The purpose of this study is to analyze the relationship between HbA1c levels and sexual function disorders in patients with diabetes mellitus in the internal room of Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City. The design of this study uses quantitative research with a cross sectional approach. The study population amounted to 74 DM patients with a sample of 42 respondents selected using purposive sampling techniques. The instruments in this study are questionnaires (IIEF) for men and (FSFI) for women. The statistical test used was the chi square test with the result of a p-value = 0.006 (< 0.05) where there was a relationship between HbA1c levels and impaired sexual function in patients with diabetes mellitus. Therefore, it is hoped that health care facilities need to integrate screening for sexual dysfunction disorders in the education program for DM patients